Rational use of soil moisture when using absorbent in crops of royal sugar beet - Kolisnyk, M. S.; Polishchuk, V. V. (AgroChemistry and Soil Science, 2023)
The article presents the results of testing, within the field experiment, a method for creating optimal moisture supply for royal beet plants by adding a granular absorbent to the soil before sowing for the rational use of soil moisture. The field experiment was carried out in 2020-2023 on podzolized heavy loam chernozem (Chernic Phaeozem) in the experimental farm of the Uman district of the Cherkasy region. The experimental design included two variants: control (without adding absorbent) and adding granular absorbent in the spring before sowing royal sugar beets at a rate of 20 kg/ha. We grew sugar beet hybrid Uman CHM 90, bred at the Uman Experimental Tobacco Station. It was determined that the introduction of absorbent granules into the soil before sowing mother sugar beets contributed to a better supply of moisture to the plants. Field soil moisture at the beginning of emergence of seedlings was higher by 5.3 %, in the phase of full emergence – by 8.4 %, in the phase of closing leaves in the rows – by 5.7 % compared to the control. The results of observations showed that improved provision of plants with moisture contributed to more intensive growth and development of mother roots of sugar beet. Analysis of the fractional composition of mother root crops revealed that when adding absorbent, the yield of planting root crops with an optimal (normative) weight of 101–600 g was high; their share was 79.0 %. With regulated moisture supply to plants, the yield of root crops weighing up to 100 g decreased. But at the same time, the number of large-sized root crops increased by 1.2 % – more than 800 g and by 2.6 % – weighing 600–800 g, which are not planting crops and are discarded. The results of the experiment indicate the advisability of continuing to study the effectiveness of using the absorbent when adding it to the soil before sowing mother sugar beets, in particular with increased seed sowing rates, which can significantly reduce the number of root crops weighing more than 600 g and help increase the efficiency of growing mother plants.